Comparative performance of different regional native sheep in Bangladesh - Hassan, M. R.; Talukder, M. A. I. (Bangladesh Veterinarian, 2012)
This study was undertaken to investigate the performance of native sheep in Bangladesh. Data were collected during 2004-2010 from sheep of the Barind, Jamuna and Coastal areas. The phenotypic characteristics did not differ significantly, but ears were shorter in Barind than in Jamuna and Coastal sheep. The coat colour was 45% white, 26% brown, 24% white brown and 3% black brown in Barind and Jamuna sheep, but white (70%) and white brown (30%) in Coastal sheep. Differences were not significant for age at first heat, age at first pregnancy and age at first lambing. Days open and post-partum ewe weight were significantly (P<0.01) different. Onset of post-partum heat, lambing interval, gestation length, number of services per pregnancy, litter size and placental weight did not differ significantly. Birth weight was significantly (P<0.05) higher in Coastal sheep than in Barind and Jamuna. Higher (P<0.05) wool yield was obtained in Coastal sheep and in the summer. Though the wool was coarse and hairy, wool from Coastal sheep had more (P<0.05) bends per inch, and was finer. Diarrhoea, pneumonia in lambs and skin diseases were the most common diseases in all sheep. Though sheep from the different areas had similar performance, better reproductive performance was obtained in the Barind sheep. DOI: http://dx.doi.org/10.3329/bvet.v28i2.10692 Bangl. vet. 2011. Vol. 28, No. 2, 85 94